Comparison of Two Different Protocols for the Treatment of Acute Escherichia coli Mastitis in Dairy Cattle - Hamidi-Sofiani, Vahideh; Hamali, Hossein; Nofouzi, Katayon (Journal of Buffalo Science, 2017)
E-coli mastitis is one of the most frequent causes of environmental mastitis in the dairy cattle worldwide. The purpose of this field study was to compare the efficacy of ceftiofur (HCL) in conjunction with supportive measures versus supportive measures alone for treatment of dairy cows affected with naturally occurring acute form of E. coli mastitis. From January 2014 to December 2016 a total number of 100 cows naturally affected by acute E-coli mastitis randomly were allocated into two groups. A milk sample from the affected quarter was collected for bacteriological tests on the first day of treatment. In group A (control), fifty cows received ceftiofur (HCL) 1mg/5kg/BW, flunixin meglumine 2.2mg/kg, calcium borogluconate 40%, 250ml and hypertonic saline (Nacl 7.2 %,) 5ml/kg. In group B (treatment, n=50), cows received the same drugs mentioned for group A, except ceftiofur (HCL) which replaced by placebo. In the group A, 41cows (82%) and in the group B, 2 cows (4%) were survived respectively. The rates of quarter health recovery in the groups A and B were 31.7% and 0% respectively. The differences between two groups were significant (P≤0.01). In conclusion our results indicated that treatment of cows affected with naturally occurring acute form of E. coli mastitis without application of effective antibiotic(s) such as ceftiofur (HCL) and fluid therapy almost impossible.